Influence of thunderstorm cloud on the performance of satellite-to-ground quantum link and parameters simulation - Min NIE; Li SHI; Guang YANG; Chang-xing PEI (Tongxin xuebao)
In order to investigate the effect of thunderstorm cloud on the performance of satellite-to-ground quantum link,according to the extinction cross section and the number concentration distribution function of the charged particle in the thunderstorm cloud,the relationships among the particle concentration,charge density and link attenuation of charged particles in atmosphere were established.The relationship between the atmospheric concentration of charged particles,the charge density on the average channel capacity,channel fidelity,channel survival function and bit error rate of quantum key distribution system were put out.The simulation results show that the thunderstorm cloud has a significant effect on the performance of the satellite-to-ground quantum link.So in order to improve the reliability of satellite-ground quantum communication,the system parameters should be adjusted according to the forecast of the thunderstorm cloud.